Studi Kasus: Asuhan Kebidanan Menggunakan Telur Ayam Kampung Dan Telur Ayam Boiler Terhadap Luka Perineum - Fenni Valianda Amelia Ramadhan; Lilik Sumiati; Magdalena Tri Putri Apriyani (STIKes MERCUBAKTIJAYA, 2023)
e causes of maternal death in Indonesia in 2019 were still dominated by bleeding (1,280 cases), hypertension (1,066 cases), infection (207 cases). One of the risk factors for perineal infection is prolonged healing of perineal wounds. Research to measure the effect of giving broiler chicken eggs on the healing of perineal wounds in postpartum mothers. This research method is to use a case study to introduce the administration of boiled free-range chicken eggs and boiled chicken boiler eggs for perineal wounds in postpartum mothers. This activity was carried out on two postpartum mothers who were in the PMB Midwife K area on July 3 2023-July 14 2023 and each postpartum mother was given the intervention of providing boiled free-range chicken eggs and boiler chicken eggs. The results of this research are that postpartum mothers who were given free-range chicken egg intervention experienced a significant decrease, namely with a score of 1, compared to postpartum mothers who were given free-range chicken egg intervention, namely with a score of 3. Researchers are expected to be able to use the intervention of giving free-range chicken eggs and by providing boiled chicken eggs as a form of intervention that helps reduce perineal wounds in postpartum mothers.